Investigation of ΔE Effect on Vibrational Behavior of Giant Magnetostrictive Transducers - M. Sheykholeslami; Y. Hojjat; M. Ghodsi; K. Kakavand; S. Cinquemani (Shock and Vibration)
Resonant magnetostrictive transducers are used for generating vibrations in the sonic and ultrasonic range of frequency. As the mechanical properties of magnetostrictive materials change according to different operating conditions (i.e., temperature, mechanical prestress, and magnetic bias), the vibrational behavior of the transducer changes too. ΔE effect is the change in the Young modulus of the ferromagnetic material and it has to be considered as it leads to changes in the dynamics of the transducer. This paper deals with the study of such effect from both theoretical and experimental point of view. ΔE effect on behavior of the transducer based on Terfenol-D is analytically described as a function of different operating conditions focusing on effects on resonance frequency, mode shape, and moreover experimentally the quality factor. Results of resonance frequency prediction have been validated with experiments and good agreement has been seen.